The effects of encapsulation process involving arabic gum on the metabolites, antioxidant and antibacterial activity of kombucha (fermented sugared tea) - Mohsin, Aliah Zannierah; Mat Nor, Nor Arifah; Muhialdin, Belal J.; Mohd Roby, Bizura Hazida; Mahmood Abadl, Muna; Marzlan, Anis Asyila; Hussain, Norhayati; Meor Hussin, Anis Shobirin (Elsevier, 2022)
This study aimed to evaluate the effects of spray drying using arabic gum as encapsulating agent on the physicochemical, antioxidant and antibacterial properties of kombucha tea, and the significant metabolites changes were determined using 1H-NMR analysis. The physicochemical properties result of the spray-dried kombucha were 16.33±0.58 Brix° for total soluble solid, 3.48±0.13% for moisture content, 0.25±0.34 for water activity, 3.28±0.03 for pH, 0.42±0.004 g/cm3 for bulk density, and 47.27±2.50% for wettability. The antibacterial activity significantly increased (p<0.05) after the kombucha fermentation, while no significant effects (p>0.05) were observed for the spray drying process on the activity. Major metabolites changes were observed for the significant decline of sucrose (17.8626 mmol/L) in sugared tea, and increased ethanol (1.8393 mmol/L) and glucose (2.6751 mmol/L) in the fresh kombucha. The acetic acid was significantly reduced (0.053 mmol/L), and the ethanol was degraded in the spray-dried kombucha. The results indicated that the spray drying process using 10% arabic gum could improve kombucha's physicochemical properties and sustain its antioxidant and antibacterial activities. Moreover, the spray drying process caused ethanol degradation, making kombucha safe for alcohol allergic and Halal concerned consumers.